In Silico Study of the Potential Inhibitory Effects on Escherichia coli DNA Gyrase of Some Hypothetical Fluoroquinolone-Tetracycline Hybrids - Ioana-Andreea Lungu; Octavia-Laura Oancea; Aura Rusu (MDPI AG, 2024)
Background/Objectives: Despite the discovery of antibiotics, bacterial infections persist globally, exacerbated by rising antimicrobial resistance that results in millions of cases, increased healthcare costs, and more extended hospital stays. The urgent need for new antibacterial drugs continues as resistance evolves. Fluoroquinolones and tetracyclines are versatile antibiotics that are effective against various bacterial infections. A hybrid antibiotic combines two or more molecules to enhance antimicrobial effectiveness and combat resistance better than monotherapy. Fluoroquinolones are ideal candidates for hybridization due to their potent bactericidal effects, ease of synthesis, and ability to form combinations with other molecules. Methods: This study explored the mechanisms of action for 40 hypothetical fluoroquinolone-tetracycline hybrids, all of which could be obtained using a simple, eco-friendly synthesis method. Their interaction with Escherichia coli DNA Gyrase and similarity to albicidin were evaluated using the FORECASTER platform. Results: Hybrids such as Do-Ba, Mi-Fi, and Te-Ba closely resembled albicidin in physicochemical properties and FITTED Scores, while Te-De surpassed it with a better score. Similar to fluoroquinolones, these hybrids likely inhibit DNA synthesis by binding to enzyme-DNA complexes. Conclusions: These hybrids could offer broad-spectrum activity and help mitigate bacterial resistance, though further in vitro and in vivo studies are needed to validate their potential.